Latent profiles of perfectionism and self-compassion: further validation of the tripartite model of perfectionists in South Korea - Hyun-joo Park (Frontiers in Psychology)
The tripartite model of perfectionism comprising maladaptive, adaptive, and non-perfectionists, has been consistently supported in the literature. However, the conceptual grounds of the grouping variables which distinguish maladaptive and adaptive perfectionists are relatively weak. Drawing on the robust conceptual intersections of perfectionism and self-compassion and employing Latent Profile Analysis, this cross-sectional study purported to validate the tripartite model of perfectionism with South Korean college students. Data were collected from 375 South Korean college students through an online survey. Participants completed an online survey assessing their levels of perfectionism, self-compassion, depression, psychological distress, self-esteem, and life satisfaction. Latent Profile Analysis revealed three distinct groups of maladaptive perfectionists, adaptive perfectionists, and non-perfectionists, categorized by varying levels of perfectionism and self-compassion. Psychological characteristics of the three groups were illuminated by their mean differences across depression, psychological distress, self-esteem, and life satisfaction. Self-compassion may assist as a key differentiator between adaptive and maladaptive perfectionists, despite their shared perfectionistic tendencies. Implications for the study findings and directions for future research were discussed.